Poetry in Teaching Grammar to the Advanced Users of Polish as a FL - Wysocka, Marzena S. (Theory and Practice of Second Language Acquisition, 2019)
The article offers an insight into problematic issues the advanced learners of Polish as a FL cope with in terms of grammar in speaking and writing. It opens with a brief insight into teaching literature, poetry including, in a FL classroom. What follows includes types of poems and their potential to be used in the teaching context, mainly when teaching grammar. Having presented the scope of linguistic problems experienced by the users of Polish as a FL, the type and frequency of grammatical problems are discussed. Polish grammar-based issues the foreigners struggle with constituted the main area of the research conducted among 146 students of the Polish Language Course attending the School of Polish Language and Culture at the University of Silesia in Katowice, Poland. The findings come from oral and written assignments produced by the sample in question, and, most frequently, reflect grammatical mistakes that are persistent and difficult to eliminate from the linguistic repertoire. Given that, ways of using poetry as a means of a “grammar refresher” are suggested. These include a few examples of activities based on poems to be used when trying to overcome particular linguistic difficulties, together with implications for teachers raising students’ language awareness and developing reflection on language per se.